Evaluacion preliminar de tecnicas de crioconservacion en una accesion de Solanum phureja - Villa, A.L.=700 1 Sanchez, A.M.; Valbuena, R.I.; Escobar, R.
(Es, En)
Ilus., 36 ref.
Keywords: SOLANUM; CONGELACION; CONSERVACION BIOLOGICA; ENCAPSULACION; DESHIDRATACION; VITRIFICACION; REGULACION DEL CRECIMIENTO; COLOMBIA; SOLANUM PHUREJA; REVISTA CORPOICA